2013
DOI: 10.1523/jneurosci.4950-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and Separable Roles for Endogenous CRY1 and CRY2 within the Circadian Molecular Clockwork of the Suprachiasmatic Nucleus, as Revealed by the Fbxl3AfhMutation

Abstract: The circadian clock of the suprachiasmatic nucleus (SCN) drives daily rhythms of behavior. Cryptochromes (CRYs) are powerful transcriptional repressors within the molecular negative feedback loops at the heart of the SCN clockwork, where they periodically suppress their own expression and that of clock-controlled genes. To determine the differential contributions of CRY1 and CRY2 within circadian timing in vivo, we exploited the N-ethyl-N-nitrosourea-induced afterhours mutant Fbxl3Afh to stabilize endogenous C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 37 publications
(2 reference statements)
4
56
0
Order By: Relevance
“…The circadian period is also sensitive to the relative abundance of CRY isoforms, CRY1 and CRY2. Analysis of the compound Cry and Fbxl3 mutants has revealed that, although CRY2 is a negative regulator within the SCN clockwork, it is less potent than CRY1 and indeed antagonizes CRY1 inhibition (Anand et al 2013). Under normal circumstances, circadian period is therefore set by the abundance and cellular localization of CRY1 and CRY2 and these competing ligases.…”
Section: Setting the Speed Of The Scn Molecular Clockmentioning
confidence: 99%
See 1 more Smart Citation
“…The circadian period is also sensitive to the relative abundance of CRY isoforms, CRY1 and CRY2. Analysis of the compound Cry and Fbxl3 mutants has revealed that, although CRY2 is a negative regulator within the SCN clockwork, it is less potent than CRY1 and indeed antagonizes CRY1 inhibition (Anand et al 2013). Under normal circumstances, circadian period is therefore set by the abundance and cellular localization of CRY1 and CRY2 and these competing ligases.…”
Section: Setting the Speed Of The Scn Molecular Clockmentioning
confidence: 99%
“…In the absence of VPAC2 expression, ERK/MAPK and pCREB signaling in the SCN is responsive to retinal activation at all circadian phases. This loss of a "circadian gate" is likely the result of a 2011b andAn et al 2013. ) proportion of desynchronized SCN neurons being in the responsive phase at any time point ).…”
Section: Role Of Vip: a Master Synchronizer With The Power To Desynchmentioning
confidence: 99%
“…CRY2 has a critical role in being the power of balance and tuning the circadian period by opposing the action of CRY1 and thereby denying CRY1 access to DNA targets too early (Anand et al, 2013).…”
Section: Mechanistic Basis Of the Associationsmentioning
confidence: 99%
“…Here, the cryptochrome circadian clock 2 (CRY2) and cryptochrome circadian clock 1 (CRY1) proteins are the key repressors in the core of the circadian clock (Dardente et al, 2007;Ozturk et al, 2007;Ye et al, 2011Ye et al, , 2014. However, CRY2 has a key role in balancing the expression of cryptochromes, as it not only acts as a general repressor, but also opposes in specific the actions of CRY1 and inhibits CRY1 from accessing to its targets too early (Anand et al, 2013). See Fig.…”
Section: Introductionmentioning
confidence: 99%